Rapid Prototyping and 3D Modeling of Osteotomy Jigs and Drill Guides in Hand and Wrist Surgery. Issue 3 (September 2016) - Kalamaras, Michael; McEniery, Paul; Thorn, Kate; Bindra, Randy
Abstract : Computer-generated 3D modeling, prototyping, and custom jig fabrication have gained popularity in a short space of time in hand and wrist surgery. Currently used applications include custom jig fabrication for the correction of malunion and other deformities, computerized motion analysis of carpal and forearm kinematics, and 3D prints and renders for visual planning and analysis in skeletal pathology and trauma. Authors are reporting improvements for a variety of reasons, including identifying new carpal and forearm kinematic patterns and pathology, decreased planning and fluoroscopy times, more efficient surgery, and greater accuracy. Commercially available services offering this technology are becoming popular. Some centers are performing these services in-house, which has become easier with the availability of free software and relatively inexpensive 3D printers. The infancy of these techniques in hand and wrist surgery preclude the presence of long-term clinical studies, cost-benefit analysis, and randomized controlled trials, which will undoubtedly come with time. 3D preoperative planning and custom jig fabrication is a compelling addition to the hand and wrist surgeons' practice, and has been well received in the literature. Improved access to desktop planning and 3D models will see the use of this technology expand. Future developments may include 3D-printed patient-specific prostheses and bone scaffolds.